Preventing burnout: Community health worker perspectives on professional development and emotional labor overload - A qualitative descriptive study - Meshack Achore; Martine Hackett; Tatiana Ramirez (PLoS ONE, 2026)
Introduction Community health workers (CHWs) play a critical role in advancing health equity by bridging underserved communities with health and social services. However, expanding responsibilities, emotional labor, and fragmented service systems contribute to burnout. While prior research has examined CHW burnout in urban, rural, and crisis contexts, little is known about how burnout is experienced and mitigated in suburban settings characterized by geographic dispersion and administrative fragmentation. This study explored how CHWs in suburban Long Island, New York, experience emotional labor overload and the strategies they use, individually and organizationally, to prevent burnout. Methods We conducted a qualitative descriptive study using purposive and snowball sampling and recruited 10 CHWs from Nassau and Suffolk counties in New York. Data were collected through ten semi-structured interviews and five participant observations. Participants were primarily women aged 35–44 years, most of whom (86%) worked in Nassau County and reported 2–5 years of experience. Transcripts were analyzed thematically using Braun and Clarke’s six-step framework in ATLAS.ti. Results Two overarching themes emerged: (1) Creating a healthy work-life balance, in which CHWs managed burnout by setting boundaries and practicing self-care; and (2) Building support structures in the workplace, where organizational supports such as supervision, peer collaboration, and ongoing training promoted resilience. Participants emphasized the importance of self-care rituals, spiritual grounding, and collegial networks as protective factors against emotional exhaustion. Conclusions Burnout among suburban CHWs is shaped by the interaction of individual coping practices and organizational conditions within fragmented service systems. Strengthening supervision, peer support infrastructure, and professional development opportunities may enhance workforce resilience and sustainability. Investments in organizational support structures are critical to sustaining CHWs’ capacity to promote health equity.